Método e umidade de colheita na qualidade de semente de milho variedade - Nascimento, Andressa Fernandes do (2013)
The use of corn varieties adapted to the environmental variations between years and the agriculture of minimum investment may be an alternative for small farmers. It is usual the use of own seed which came from these varieties planted in small farms. This way good quality seeds production by these farmers is fundamental to improve the productive capacity of the culture. This study aimed to determinate the most adequate method and humidity to obtain high quality variety corn seeds. The experiment was carried out in randomized block design with four replications. Treatments were distributed in factorial scheme (6x2+1), being the 1st factor: harvest moments, which were subdivided in humidity and days; four values of humidity 22%, 19%, 16% and 3%, the latter being named as harvest point as well and two intervals of days 7 and 14 days after harvest point; 2nd factor: harvest methods: manual and mechanic harvest; and additional treatment: harvest in physiological point of maturation, with 35% of humidity. Characteristics evaluated included percentage of normal seedlings (germination) and abnormal seedlings and dead seeds, obtained by germination test, emergence, emergence speed index, final time, average emergence time, coefficient of variation time, emergence synchrony index, uncertainty and relative frequency of emergency, obtained by emergence test in sand, vigor, obtained by cold test and mechanical damages. It was concluded that seed humidity did not interfere in germination and vigor of seed harvested manually; humidity at 22%, mechanical harvest damaged the obtaining of seeds with higher percentage of germination, vigor and emergency; and seed very humid (22%) or very dry (<13%) were more susceptible to mechanical damages.